Execution of Blockchain in The World of Archive - Dimas Wijaksono, Satrio; Hadi Trianto, Ramadhan; Febri Ikhtiarman, Awal; Amalia, Rizka; Jannah, Fadiyatul (Blockchain Frontier Technology, 2022)
Archiving certification, especially in electronic archiving, remains a problem in the archiving world. The solution to this problem is the blockchain technology first used in digital currencies. Blockchain is believed to have had a significant impact on archive management. This study aims to consider the application of blockchain technology in archiving, including Features, application examples, opportunities, and challenges related to blockchain technology inconsistencies in archive science. This study uses a qualitative approach using literature data sources from various disciplines related to the basic concepts of archival science as the basis for analysis. The results of this study show that various possibilities can be developed on the blockchain. The contradiction between the implementation issues, especially in Indonesia, and the basic concepts of blockchain technology and archive science. This study concludes that further research is needed to ensure that blockchain technology adheres to archive science's basic concepts and principles, especially concerning reliability.